RISK FACTORS RELATED TO KARBAMAT PESTICIDE POISONING AND ORGANOPHOSPHATE IN RICE FARMERS IN MASANGAN VILLAGE KULON KABUPATEN SIDOARJO - Nur Eka Vutrianingsih; Ikrimatuz Zulfa; Jojok Mukono (Universitas Airlangga, 2020)
In the efforts to increase product of rice plant crops, the use of pesticides to excerminate pest can not be avoided. However rice plant farmers incline carry out spray of pestisides which abused impact can increase poison inciden of farmers. The objective of this research was to know about risk factors related to pesticide poison incidence because use carbamates pesticides and organophosphates pesticides in Masangan Kulon Village Subdistrict Sukodono District Sidoarjo. The type of this research is analytic observational with cross sectional approach. Sample of this research is 28 farmers. The collected data were analyzed analytically using Fisher Exact Test. The variable in this research were age, sex, educational level, length of work,the using Personal Protection Equipment, length of exposure, knowledge, total of kind pesticides, and management practices of pesticides. Checking cholinesterase enzyme value in the blood with Kinetic Photometric DGKC by BBLK of Surabaya.The result of this research showed as 2 farmers (7,1%) has pesticides’s poisoning. The result of statistic test showed there was no significant relationship between sex (p = 0,091), educational level (p = 0,553),length of work (p = 0,288), the using Personal Protection Equipment (p = 0,622), total of kind pesticides (p = 1,000), knowledge (p = 0,549), and management practices of pesticides (p = 1,000) with pesticides poisoning. There was significant relationship between age (p = 0,001) and length of exposure (p = 0,001) with pesticides poisoning. Conclution of this research counseling from relevant agencies about pesticides, periodic checking cholinesterase enzyme of farmers and observe pesticide sale distribution in village.Keywords : Pesticides, Carbamate and Organophosphate, Cholinesterase